Yhteysalusliikenteen toimintamallien vertailu ja riskiarviointi - Ojala Lauri (University of Turku, 2025)
This is a study commissioned by the Ministry of Transport and Communications Finland (MoTC) on operating and public procurement models for small island ferry traffic in the archipelago of Mainland Finland.
The work was carried out for MoTC in March-September 2023 as part of the Government's broader need for information on the prospects for the development of small island ferry traffic and related measures.
The report examines the benefits, drawbacks, and risks of four main operating models for small island ferry traffic in Mainland Finland for key stakeholders (see below). The focus of the analysis includes the nature of route networks, fleet composition, contract durations, and continuity management of ferry operations. The study also touches upon the impact of organizational size on operational continuity and efficiency and provides an overview of ferry traffic in the Åland Islands, Sweden, and Estonia. In models 1) and 2), the current 5-year (Models 1a & 2a) and a 10+5-year period (Models 1b & 2b) were examined:
1) The current procurement model: vessels owned & operated by private operators or a state-owned firm
2) The package tendering model, where tenders comprise route sets that are wider than the current ones
3) A commercial company, which operates the fleet (3a) or where vessel operation is tendered (3b)
4) The state agency model, where an agency owns and operates (4a), or just owns the fleet (4b)
In 2022, about 260,000 passengers were transported in mainland Finland's publicly procured small island ferry services tendered by Southwest Finland Centre for Economic Development, Transport and the Environment, a government authority. In September 2023, there were four main competitors and their respective subcontractors in this approximately €17 million market. Together, they employed fewer than 100 staff, operated 15 vessels, and had 6 reserve vessels. The industry is small and highly concentrated, with the state-owned FinFerries group (Suomen Lauttaliikenne Oy) holding a 70% share of the market's monetary value as of May 2023.
In the 2020s, regulations concerning the environment, safety, and other aspects of the industry are expected to become more stringent. Although the age structure of the fleet has improved in the last few years, some vessels are still quite old, and the reserve vessels are extremely aged. The conditions to develop the industry and introduce new, safer, and more environmentally friendly vessels do exist.
When considering a timeframe of 10-20 years, two main options appear to suit best to meet changes in industry regulations and the operating environment. Ranking these models in terms of superiority is a political decision, including the possibility of continuing with the current arrangements (Model 1a):
A contract model of at least 10+5 years or even 20 years, where the current routes are consolidated into 4-7 larger traffic areas (Model 2b), or
A state-owned fleet company operating its vessels (Model 3a).
Both options require determined, clear, and long-term political guidance from the Finnish government and responsible ministries. This guidance should also be communicated clearly to the authority responsible for the tendering process, especially in Model 2b. Without such direction, the authority cannot, on its own, harness the unique potential for ferry traffic development. Both models also emphasize the importance of the determined and long-term ownership guidance provided by the state-owned company FinFerries.
Keywords: small island ferry traffic, public procurement, organizational models for tendering public transport services, archipelago transport services, risk assessment